Head and Pelvic Movement Asymmetries at Trot in Riding Horses Perceived as Sound by Their Owner. (September 2015) - Rhodin, M.; Egenvall, A.; Andersen, P.H.; Pfau, T.
Abstract : Reasons for performing study: Recent studies evaluating owner sound horses have identified a large proportion of horses with motion asymmetries but the prevalence, type and magnitude of asymmetries have not been investigated. The increasing use of objective lameness evaluation necessitates a further characterisation of the differences between lameness and motion asymmetries. Objectives: To investigate prevalence, and quantify type and magnitude of motion asymmetries during straight‐line trot in riding horses, perceived sound by their owners. Study design: Cross‐sectional prospective study. Methods: Vertical head and pelvic movement symmetry was measured in 220 Warmblood riding horses, all functioning in daily work and considered sound by their owners; 100 of these individuals had been included in a previous report [1]. Body‐mounted uni‐axial accelerometers were used and differences between maximum and minimum head (HDmax, HDmin) and pelvic (PDmax, PDmin) vertical displacement between left and right forelimb and hindlimb stances were calculated during straight‐line trot. Previously used symmetry thresholds (absolute differences >6 mm for the head and >3 mm for the pelvic variables) were used. Results: The thresholds for symmetry were exceeded for 159 horses (72%) for at least one variable, HDmax (n = 41, mean 12.7 mm, s.d. 5.5), HDmin (n = 58, mean 14.3 mm, s.d. 7.1), PDmax (n = 87, mean 6.5 mm, s.d. 3.10), PDmin (n = 77, mean 5.7 mm, s.d. 2.1). Contralateral and ipsilateral concurrent fore‐ and hindlimb asymmetries were detected in 41 and 49 horses, respectively. Conclusions: A surprisingly large proportion (72%) of horses perceived as sound by their owner showed movement asymmetries during straight‐line trot. It is not known to what extent these asymmetries are related to pain or mechanical abnormalities as opposed to 'normal variation' and this leads to 2 potential welfare problems – either too many horses in training are actually 'lame' or many horses categorised as 'lame' have no locomotor system disease. Ethical animal research: This study was conducted within guidelines of the participating sites institutional animal care and use procedures (C 206/10, C48/13) and informed consent for data collection was obtained from the horse owners prior to the study.Source of funding: None.Competing interests: None declared.